The improvement of funding business operations for the local enterprises in the Republic of Uzbekistan through issuing financial securities by means of the Tashkent Stock Exchange - Abduganiev , Abdulaziz (GREEN ECONOMY AND DEVELOPMENT, 2024)
The goal of this article is to show a meaning of the new funding ratio, which is the 60/40 funding ratio besides how it actually operates and the benefits to integrate the cooperation between the Tashkent Stock Exchange and the medium-sized, large private enterprises, after this would lead to spur local private firms to go public or issue corporate bonds in order to raise capital for business operations and other projects.